2016
DOI: 10.1007/s00423-016-1540-y
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic sentinel node navigation surgery for early gastric cancer: a prospective multicenter trial

Abstract: The infrared ICG imaging accurately detected the lymphatic basin and SNs with occult metastasis in SN-navigated gastrectomy for gastric cancer. This method was feasible even for low-volume surgeons and hospitals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 20 publications
1
35
0
Order By: Relevance
“…To overcome disadvantages in conventional marking methods, we turned to ICG‐mediated imaging, which has been applied in sentinel lymph node navigation and orientation of the liver segments . During sentinel lymph node navigation, ICG is endoscopically injected into the submucosal layer of the stomach, which is similar to our method; several previous studies have reported the safety of this method .…”
Section: Discussionmentioning
confidence: 99%
“…To overcome disadvantages in conventional marking methods, we turned to ICG‐mediated imaging, which has been applied in sentinel lymph node navigation and orientation of the liver segments . During sentinel lymph node navigation, ICG is endoscopically injected into the submucosal layer of the stomach, which is similar to our method; several previous studies have reported the safety of this method .…”
Section: Discussionmentioning
confidence: 99%
“…The results of methodological quality that presented as percentages are summarized in Figure . However, “blinding design” was clearly described in only two studies …”
Section: Resultsmentioning
confidence: 99%
“…The dual method is considered the most reliable method, but it requires considerably more operative time, and the patient preparation is not a simple task . Fortunately, NIR or fluorescent ICG guided SLN mapping in GC has been conducted by various institutions and has yielded acceptable pooled sensitivity of 0.94 (95%C1: 0.80‐0.99), although a wide variation exists (0.40‐1.00) . Thus, this meta‐analysis is performed to evaluate the diagnostic value of NIR or fluorescent ICG guided SLN mapping in GC, and to identify factors of this diagnostic performance.…”
Section: Introductionmentioning
confidence: 99%
“…Although further accumulation and analysis are necessary, we may be able to apply this method for avoiding unnecessary D2 dissection, intraoperative SN mapping and modified resection of laparoscopic gastric cancer surgey [21], [22], [23], [24].…”
Section: Discussionmentioning
confidence: 99%